KAPABILITAS KOMISI PENANGGULANGAN AIDS (KPA) DALAM PENANGANAN HIV/AIDS DI KOTA PEKANBARU TAHUN 2022 - Eliani, Lili; Harirah, Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the capabilities of the AIDS Commission (KPA) in handling HIV/AIDS in Pekanbaru City in 2022. The research was conducted using a qualitative descriptive method which aims to describe the phenomena that occur. The theory used in this research is the capability of public organizations according to Kusumasari (2014) with Institutional, Human Resources, Financial and Technical indicators. This type of research is qualitative with a descriptive approach. The data collection techniques used in this research were interviews, observation, documentation as well as note taking and recording. The research results show that the capability of the Pekanbaru City AIDS Commission (KPA) in handling HIV/AIDS can be seen from several indicators as follows: 1) Institutional capability in terms of institutional arrangements of the Pekanbaru City AIDS Control Commission is quite good with the structure and team in place. 2) The human resource capabilities of the Pekanbaru City KPA are considered to be not optimal in carrying out all their duties and functions, this is due to an inappropriate educational background. 3) Capability in terms of budget, it is known that the Pekanbaru City KPA obtains a budget or financial resources originating from the Pekanbaru City APBD with a total amount of 200 million even though what is needed is 500 million, and it is not uncommon for this budget to be disbursed in the middle of the year. So the KPA cannot work effectively in dealing with the HIV/AIDS problem in Pekanbaru City. 4) Technical capabilities in terms of logistics and information systems used by the Pekanbaru City KPA to collaborate and build coordination with related parties in efforts to handle HIV/AIDS in Pekanbaru City are classified as capable of providing information facilities for communicating and establishing cooperation with various sectors and government institutions. and non-governmental organizations. Keywords: Capability, HIV/AIDS, KPA, Pekanbaru City